Supramolecular chemistry : Concepts and perspectives - Lehn, Jean-Marie (Weinheim : VCH, 1995)
Supramolecular chemistry is a central theme not only in chemistry, but in neighboring disciplines including physics and the biological sciences. The author has introduced this notion and has been awarded the Nobel Prize for his achievements in this area. He presents here the concepts, lines of development and perspectives of this highly interdisciplinary and burgeoning field of research.Topics include molecular recognition catalysis and transport processes molecular and supramolecular devicesself-processes By placing the basic concepts into a broader perspective, the author succeeds in inspiring, stimulating and challenging the creative imagination of his reader.
Includes Bibliography 207-258p.; Index 263-271p.
Keywords: Molecular recognition; Supramolecular chemistry; Chemistry